FOSTERING THE YOUNG GENERATION BASED ON PANCASILA VALUES TO STRENGTHEN THE NATION'S CHARACTER - Teki Prasetyo Sulaksono; Kokom Komalasari; Prayoga Bestari; Yuli Kurniasih (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Young people play a strategic role in sustaining Pancasila values and the quality of democratic life in Indonesia, yet they face serious challenges due to globalization, technological disruption, and shifting social values. This article aims to analyze Pancasila-based youth development from a civic education perspective by positioning Pancasila as a foundational value, ethical orientation, and guideline for social praxis. This study employs a qualitative descriptive approach through a literature review of relevant books, research findings, and scholarly journal articles. The findings indicate that youth development should be understood as an integrated process involving civic education, youth social organizations, community environments, and digital spaces, with participatory and reflective approaches as key mechanisms for internalizing Pancasila values. Adaptive youth development that remains grounded in Pancasila values contributes to the formation of character, leadership, and social responsibility among young people. This article highlights the importance of cross-sectoral synergy in fostering a Pancasila-oriented young generation committed to unity and social justice.